Search for a structural response to the intermediate phase in Ge(x)Se(1-x) glasses - Shatnawi, M; Farrow, C; Chen, P; Boolchand, P; Sartbaeva, A; Thorpe, M; Billinge, S (2008)
Atomic pair distribution functions (PDFs) obtained from high energy x-ray synchrotron radiation and x-ray absorption fine structure measurements were performed on 18 closely spaced compositions of chalcogenide glasses (Gex Se1-x with 0.15≤x≤0.40), which span the range of the floppy to rigid phase transition in these glasses. Structural parameters such as PDF peak widths, Debye-Waller factors from extended x-ray absorption fine structure, and the first sharp diffraction peak in S (Q) were extracted as a function of composition. These parameters smoothly evolve with composition, but there are no clear discontinuities or breaks in the slope associated with the appearance of the intermediate phase (IP). Therefore, these measurements do not confirm a structural origin for the IP. © 2008 The American Physical Society.